Deaf children's non-verbal working memory is impacted by their language experience - Marshall, Chloë; Jones, Anna; Denmark, Tanya; Mason, Kathryn; Atkinson, Joanna; Botting, Nicola; Morgan, Gary (Frontiers in Psychology, 2015)
Several recent studies have suggested that deaf children perform more poorly on working memory tasks compared to hearing children, but these studies have not been able to determine whether this poorer performance arises directly from deafness itself or from deaf children's reduced language exposure. The issue remains unresolved because findings come mostly from (1) tasks that are verbal as opposed to non-verbal, and (2) involve deaf children who use spoken communication and therefore may have experienced impoverished input and delayed language acquisition. This is in contrast to deaf children who have been exposed to a sign language since birth from Deaf parents (and who therefore have native language-learning opportunities within a normal developmental timeframe for language acquisition). A more direct, and therefore stronger, test of the hypothesis that the type and quality of language exposure impact working memory is to use measures of non-verbal working memory (NVWM) and to compare hearing children with two groups of deaf signing children: those who have had native exposure to a sign language, and those who have experienced delayed acquisition and reduced quality of language input compared to their native-signing peers. In this study we investigated the relationship between NVWM and language in three groups aged 6–11 years: hearing children (n = 28), deaf children who were native users of British Sign Language (BSL; n = 8), and deaf children who used BSL but who were not native signers (n = 19). We administered a battery of non-verbal reasoning, NVWM, and language tasks. We examined whether the groups differed on NVWM scores, and whether scores on language tasks predicted scores on NVWM tasks. For the two executive-loaded NVWM tasks included in our battery, the non-native signers performed less accurately than the native signer and hearing groups (who did not differ from one another). Multiple regression analysis revealed that scores on the vocabulary measure predicted scores on those two executive-loaded NVWM tasks (with age and non-verbal reasoning partialled out). Our results suggest that whatever the language modality—spoken or signed—rich language experience from birth, and the good language skills that result from this early age of acquisition, play a critical role in the development of NVWM and in performance on NVWM tasks.